2012
DOI: 10.1136/annrheumdis-2012-202159
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Statin use and changes in pain, function and structural progression: a longitudinal study of persons with knee osteoarthritis

Abstract: Statin use was not associated with improvements in knee pain, function or structural progression over the 4-year study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 23 publications
(31 reference statements)
2
50
0
Order By: Relevance
“…These results are in line with another study that examined associations between statin use and joint-related symptoms. Riddle et al found no association between statin use and knee pain in a sample of 2,207 men and women with or at high risk of OA (12). However, 2 studies that examined associations between statin use and symptomatic radiographic OA did find significant associations (9,10).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These results are in line with another study that examined associations between statin use and joint-related symptoms. Riddle et al found no association between statin use and knee pain in a sample of 2,207 men and women with or at high risk of OA (12). However, 2 studies that examined associations between statin use and symptomatic radiographic OA did find significant associations (9,10).…”
Section: Discussionmentioning
confidence: 98%
“…If statins do indeed prevent OA, it would be expected that statins also prevent OA-related symptoms. In a study among men and women with OA or with a high risk of OA, no association was found between statin use and knee pain (12). However, as most participants in that study had knee pain at baseline, the study does not provide insight in potential preventive effect of statin use on symptoms.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although a large longitudinal study in the OA found no such association [48], it is possible that statins affect lipid dysregulation particularly in generalised (i.e. systemic) forms of OA where several joints are involved [49].…”
Section: Role Of Statins -Common Aetiology?mentioning
confidence: 99%